Hakikat Media Pembelajaran Membaca di Kelas Tinggi - Nurul Handini; Fenika Ardiyani; Tiara Ramadhani; Juni Sahla Nasution (Universitas Maritim AMNI Semarang, 2024)
The use of learning media in high-level reading classes plays an important role in improving students' reading abilities. Various types of learning media, including visual, audio-visual, and interactive computer-based materials, are used for this purpose. The process of utilizing learning media includes analysis of student characteristics, design, development, implementation and evaluation of learning outcomes. This learning media has various functions in teaching reading, such as facilitating access to information, motivating students, helping understanding and retention of information, fostering critical thinking skills, enabling differentiated learning, encouraging independent learning, and developing digital literacy skills. In addition, many studies have investigated the effectiveness of various learning media, such as comics, modules, computer-based interactive learning, and picture cards, in increasing elementary school students' interest in reading and academic achievement.